Management Strategy of PAUD Permata Bunda Binubu Baru Nagari Sontang Cubadak Padang Gelugur District - Ardila, Fernanda; Ismaniar, Ismaniar (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2024)
This research is motivated by the development of the Permata Bunda Binubu Baru PAUD institution in recent years. This is presumably due to the institutional management strategy carried out by the manager. Therefore the public interest in this institution is also very good. This study aims (1) to describe the management plan for PAUD Permata Bunda. (2) to describe the organization of Permata Bunda PAUD management. (3) to describe the implementation of the management of Permata Bunda PAUD. (4) to describe the oversight of Permata Bunda PAUD management. This research is a qualitative research with a descriptive approach. The setting of this research was conducted at Permata Bunda Binubu Baru PAUD, Nagari Sontang Cubadak, Padang Gelugur District, Pasaman Regency. Sources of data for this research were obtained from school principals, educators and also guardians of Permata Bunda PAUD students. Data collection techniques used in this study were observation, interviews and documentation. The validity of the data obtained from this study is the triangulation of sources, techniques, and time. The results of the study show that (1) there is a planning for PAUD Permata Bunda in the form of a long-term work plan and a short-term work plan. (2) the organization of Permata Bunda PAUD takes the form of selecting and recruiting prospective educators, organizing educator training, organizing educator salaries. (3) the implementation of PAUD Permata Bunda in the form of PAUD accreditation, religious activities, and renewal of PAUD buildings. (4) supervision of Permata Bunda PAUD in the form of supervising dropping off and picking up young children using the school bus, as well as supervision while at school.